Mapping the Research Landscape of the Knowledge Management in the Higher Education Sector in Algeria Using the ASJP database during (2014-2022) - Amalou , Sif Islem; Naga , Nahla (Finance and Business Economies Review, 2023)
The aim of this study is to examine the issue of knowledge management in the higher education sector in Algeria during the past decade, by tracking the development of articles published through the Algerian Scientific Journal Platform ASJP for the period between 2014-2022, which contain in their titles, keywords and summaries the word "knowledge management". and "Higher Education", where the method of bibliometric analysis was adopted to measure the development of scientific publishing for this subject, and the study revealed that the number of published articles reached 29, where most of the articles were in Arabic and a few were in English, and there are leading journals in publishing such articles They are the "Review of Human Sciences," " Economic Researcher Review," and " Dirassat Journal Economic Issue". As for the authors' affiliation universities, we have the University of Batna 1, which is distinguished by a large number of affiliated authors who have published articles on this subject compared to other universities. The researchers who have published the highest number of articles on this topic are the following A. Nebouia, H.S El Hartessa, I. Benziane, N.H Bouteba, O. Oueld Abed, T. Saraa, and W. Mehibel. The results and analyzes contained in this study are considered a roadmap for academics, researchers, and universities. Arsene in the future to help in the adoption of knowledge management in the higher education sector.